Effect of condensed tannins in rations of lactating dairy cows on production variables and nitrogen use efficiency. (8th January 2018) - Gerlach, K.; Pries, M.; Tholen, E.; Schmithausen, A. J.; Büscher, W.; Südekum, K.-H.
Abstract : The objective of this study was to evaluate the effect of supplemented condensed tannins (CT) from the bark of the Black Wattle tree ( Acacia mearnsii ) on production variables and N use efficiency in high yielding dairy cows. A feeding trial with 96 lactating German Holstein cows was conducted for a total of 169 days, divided into four periods. The animals were allotted to two groups (control (CON) and experimental (EXP) group) according to milk yield in previous lactation, days in milk (98), number of lactations and BW. The trial started and finished with a period (period 1 and 4) where both groups received the same ration (total-mixed ration based on grass and maize silage, ensiled sugar beet pulp, lucerne hay, mineral premix and concentrate, calculated for 37 kg energy-corrected milk). In between, the ration of EXP cows was supplemented with 1% (CT1, period 2) and 3% of dry matter (DM) (CT3, period 3) of a commercial A. mearnsii extract (containing 0.203 g CT/g DM) which was mixed into the concentrate. In period 3, samples of urine and faeces were collected from 10 cows of each group and analyzed to estimate N excretion. Except for a tendency for a reduced milk urea concentration with CT1, there was no difference between groups in period 2 (CON v . CT1; P >0.05). The CT3 significantly reduced ( P <0.05) milk protein yield, the apparent N efficiency (kg milk N/k feed N) and milk urea concentration; but total milk yield and energy-corrected milk yield were not affected by treatment. Furthermore, as estimated from 10 cows per group and using urinary K as a marker to estimate the daily amount of urine voided, CT3 caused a minor shift of N compounds from urine to faeces, as urea-N in urine was reduced, whereas the N concentration in faeces increased. As an improvement in productivity was not achieved and N use efficiency was decreased by adding the CT product it can be concluded that under current circumstances the use in high yielding dairy cows is not advantageous.